Mekong-Ganga Cooperation Initiative : Analysis and Assessment of India's Engagement with Greater Mekong Sub-region - Swaran Singh (Institut de recherche sur l'Asie du Sud-Est contemporaine, 2007)
From October 2006, India holds the Chair of the Mekong-Ganga Cooperation Initiative (MGCI). Cambodia and Thailand have held this position for three years each before India, and in that order. MGCI was launched on 10th November 2000 in Vientiane (Laos) and aims at rekindling the cultural links between India and the five riparian states of the Mekong River, namely, Cambodia, Laos, Myanmar, Thailand and Viet Nam. It is from here that India seeks to strengthen connectivity through building the physical and social infrastructure in these countries. This includes roads, rails, air links and information and communication technologies as also education, culture, and imparting skills in development management and other technical areas. It is only with a robust engagement of this nature that MGCI may evolve a lasting socio-political and economic partnership with this region and take it further in enhancing India's military and strategic equations with these countries. India has taken scores of major initiatives under the MGCI and this newfound enthusiasm has also provided a boost to India's bilateral relations with each country. As this study shows, the results, however, remain a mixed bag and India needs to accelerate its footwork to implement its grand vision and to keep pace with other major stakeholders in this region. In particular, progress made by China has been far too rapid and this has put China in the lead and this remains a subject of debate both inside and outside the Mekong region.